IMPLEMENTASI PENDEKATAN KONSTRUKTIVISME TIPE SNOWBALL THROWING DALAM PEMBELAJARAN MENULIS PUISI DI KELAS VII MTS HIDAYATUL ISLAMIYAH BUMIREJO - Bisarul Ihsan (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2019)
This study aims to (1) describe the results of learning to write poetry using the Snowball Throwing type constructivism approach, (2) describe student activities, (3) describe students' responses to the learning process using the Snowball Throwing type constructivism approach. The results of this study are (1) the acquisition of students' cognitive abilities in understanding learning about poetry with the results of an average value of 90.2. (2) Student activities during the learning process are quite active, with the percentage of active students equaling 91.3 (21 students), and inactive students 8.7 (2 students). (3) Results of student responses with the percentage of students who responded to the Yes category by 66.92%, Less categories by 32.98%, and No categories by 0%.